Small but not isolated: a population genetic survey of the tropical tree Cariniana estrellensis (Lecythidaceae) in a highly fragmented habitat - Guidugli, M C (Heredity (Edinb), 2016)
Here, we explore the mating pattern and genetic structure of a tropical tree species, Cariniana estrellensis, in a small population in which progeny arrays (n=399), all adults (n=28) and all seedlings (n=39) were genotyped at nine highly informative microsatellite loci. From progeny arrays we were able to identify the source tree for at least 78% of pollination events. The gene immigration rates, mainly attributable to pollen, were high, varying from 23.5 to 53%. Although gene dispersal over long distance was observed, the effective gene dispersal distances within the small population were relatively short, with mean pollination distances varying from 69.9 to 146.9 m, and seed dispersal distances occurring up to a mean of 119.6 m. Mating system analyses showed that C. estrellensis is an allogamous species (t(m)=0.999), with both biparental inbreeding (t(m)−t(s)=−0.016) and selfing rates (s=0.001) that are not significantly different from zero. Even though the population is small, the presence of private alleles in both seedlings and progeny arrays and the elevated rates of gene immigration indicate that the C. estrellensis population is not genetically isolated. However, genetic diversity expressed by allelic richness was significantly lower in postfragmentation life stages. Although there was a loss of genetic diversity, indicating susceptibility of C. estrellensis to habitat fragmentation, no evidence of inbreeding or spatial genetic structure was observed across generations. Overall, C. estrellensis showed some resilience to negative genetic effects of habitat fragmentation, but conservation strategies are needed to preserve the remaining genetic diversity of this population.